Caregiver burden and associated factors amongst carers of women with advanced breast cancer attending a radiation oncology clinic in Nigeria - Ikechi E. Jite; Adedotun A. Adetunji; Ayorinde M. Folasire; Joshua O. Akinyemi; Segun Bello (AOSIS, 2021)
Background: The responsibility of caring for patients with advanced cancer in sub-Saharan Africa is mostly shouldered by family members because of paucity of institutional facilities. There is a growing concern that the number of women needing treatment for advanced breast cancer is rising at an unprecedented rate in Nigeria. Aim: To assess the caregiver burden and its associated factors amongst family caregivers of women with advanced breast cancer. Setting: The study was conducted at the radiation oncology clinic of the University College Hospital, Ibadan, Nigeria. Methods: A cross-sectional descriptive study was conducted amongst 157 eligible family caregivers of women with advanced breast cancer. The family caregivers completed an interviewer-administered questionnaire, which included the socio-demographic data, the caregiving process and the Zarit Burden Interview (ZBI). Logistic regression was used to identify factors, and ethical approval was obtained. Results: Over half (53%) of the respondents were males with spousal caregivers dominantly constituting 27.4% of all respondents, closely followed by daughters (25.5%) of the care recipients. The mean ZBI score was 29.84 ± 13.9. Most (72%) of the caregivers experienced burden. Factors associated with caregiver burden were previous hospitalisation of the care recipient (odds ratio [OR] = 3.74, confidence interval [CI]: 1.67 to 8.38) and perceived dysfunction in patients activities of daily living (OR = 2.57, CI: 1.14 to 5.78). Conclusion: Family caregivers of women with advanced breast cancer experience burden of care. Recognition of this vulnerable population and the care recipient as a dyad is a sine qua non in mitigating the burden associated with their caregiving role.